Valve-in-valve procedures for degenerated surgical and transcatheter aortic valve bioprostheses using a latest-generation self-expanding intra-annular transcatheter heart valve - Schaefer, Andreas; Demal, Till Joscha; Bhadra, Oliver D.; Grundmann, David; Voigtländer, Lisa; Waldschmidt, Lara; Schirmer, Johannes; Pecha, Simon; Schneeberger, Yvonne; Schofer, Niklas; Sörensen, Nils; Blankenberg, Stefan; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Valve-in-valve (ViV) transfemoral transcatheter aortic valve implantation (TAVI) for failing aortic surgical bioprostheses or transcatheter heart valves (THV) has demonstrated a reasonable clinical and hemodynamic efficacy. Traditionally, self-expanding (SE) supra-annular THV are considered to result in superior hemodynamics compared with balloon-expandable intra-annular THV after ViV. However, so far no data are found on latest-generation intra-annular SE THV for aortic ViV procedures which might be superior with regard to coronary access or subsequent valve reintervention. Aim We herein aim to evaluate a latest-generation SE intra-annular THV for aortic ViV procedures. Materials and methods Between May 2022 and November 2022, five consecutive patients (4/5 female with mean age of 76.2 years and mean Society of Thoracic Surgeons predicted risk of mortality score of 2.9%) received ViV TAVI using the Navitor system (Abbott, Chicago, IL, USA) for treatment of failing surgical bioprostheses or THV. Data were retrospectively analyzed according to updated Valve Academic Research Consortium 3 (VARC-3) definitions. Results At 30 days, absence of mortality and VARC-3 adjudicated clinical endpoints were documented. Echocardiography at 30 days revealed complete absence of paravalvular leakage and single-digit mean transvalvular gradients (mean of 6.0 mmHg) in all patients. Conclusion The investigated intra-annular SE THV results in excellent 30-day outcomes for aortic ViV procedures for failing surgical bioprostheses or THV. Despite the intra-annular design, hemodynamic results were excellent, even in small bioprostheses. Ease of use of this valve platform is reflected by only two cycles of resheathing in five ViV procedures with hemodynamic stability during all steps of valve deployment.